REVIEW: ANTIBACTERIAL, ANTIFUNGAL AND WOUND HEALING ACTIVITY OF NANOEMULGEL FORMULATIONS AND PHYSICAL CHARACTERISTICS - Rodhia Ulfa; Wildan Khairi Muhtadi; Urva Fresiva; Amraini Amelia (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Nanoemulgel is an emulsion preparation with a droplet size of 1–100 nm suspended in a hydrogel. This review delves into the research on the impact of incorporating excipient components in nanoemulgel formulations to create products with specific physical attributes for different active ingredients with antifungal, antibacterial, and wound-healing properties. The research approach involves comparing articles on nanoemulgel preparation formulations with different combinations of active ingredients and excipients, as well as their pharmacological effects. Enhancing the level of active ingredients and altering the excipients can boost the effectiveness of nanoemulgel formulations in combating fungi, bacteria, and promoting wound healing. The review includes articles published within the past decade. Keywords: Nanoemulgel, Pharmacological activity, Physical characteristics, Review